Disability, social inclusion and the marketing of tourist attractions. Issue 2 (1st February 2018) - Cloquet, Isabelle; Palomino, Marco; Shaw, Gareth; Stephen, Gemma; Taylor, Tim
ABSTRACT: The participation of persons with a disability (PWDs) in tourism has received growing academic interest in recent years. This paper contributes to a reflection on how accessible tourism relates to the sustainable development paradigm. To investigate this relationship, it goes beyond the question of PWDs' access to tourism services, and adopts an inclusiveness perspective. Inclusion is examined in terms of legislation, marketing and imagery, and representations of PWDs as consumers embedded within social units – and families in particular. These dimensions are explored empirically in a study of visitor attractions in Cornwall (England) based on a quantitative and qualitative content analysis of brochures and websites. The study shows that the marketing materials of Cornish visitor attractions mainly focus on access, and the imagery used largely projects quasi invisibility or provides ambiguous messages. Communication with PWDs rarely addresses the family unit, making the family tourism experience intangible in the pre-trip phase. These results point at weaker implementation of inclusiveness, which corroborates previous findings of watered down definitions of rights to tourism under neo-liberal ideologies and economic crises. The paper discusses implications for social inclusion and highlights avenues for future research.